2010
DOI: 10.1016/j.jmb.2010.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Calmodulin Disrupts the Structure of the HIV-1 MA Protein

Abstract: The MA protein from HIV-1 is a small, multifunctional protein responsible for regulating various stages of the viral replication cycle. To achieve its diverse tasks MA interacts with host cell proteins and it has been reported that one of these is the ubiquitous calcium -sensing calmodulin (CaM) which is up-regulated upon HIV-1 infection. The nature of the CaM-MA interaction has been the subject of structural studies using peptides based on the MA sequence that have led to conflicting conclusions. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 63 publications
14
27
0
Order By: Relevance
“…Tryptophan fluorescence data additionally suggested that interactions are possibly mediated by insertion of Trp 16 and Trp 36 in hydrophobic pockets of CaM (57). Although these findings agree with most of our previous (59,61) and current data, the structure of CaM⅐MA- (8 -43) clearly shows that Trp 36 is exposed to solvent and is not involved in any interaction with CaM; the orientation of the helix positions the indole group of Trp 36 away from the binding pocket (Fig.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Tryptophan fluorescence data additionally suggested that interactions are possibly mediated by insertion of Trp 16 and Trp 36 in hydrophobic pockets of CaM (57). Although these findings agree with most of our previous (59,61) and current data, the structure of CaM⅐MA- (8 -43) clearly shows that Trp 36 is exposed to solvent and is not involved in any interaction with CaM; the orientation of the helix positions the indole group of Trp 36 away from the binding pocket (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…In vivo and in vitro studies revealed that CaM interacts with additional HIV-1 proteins like Nef, Tat, and gp160 (27,34,37,52,53,56). Small-angle x-ray scattering studies have provided a global picture of CaM bound to full-length MA (57) or to short peptides derived from the MA protein (58). Our laboratory (59) and others (57,60) have shown that CaM binds directly to the MA protein in a calcium-dependent manner.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…This unfolding event also releases helix ␣6 and make it accessible to CaM. The ability of CaM to disrupt protein targets has been recently observed in studies of the interactions between CaM and the human immunodeficiency virus type-1 matrix protein (37,45,64). CaM-induced unfolding of protein targets is not unusual.…”
Section: Discussionmentioning
confidence: 89%
“…The final expressed recombinant protein included an in-frame N-terminal polyhistidine tag that was not removed due to the proteolytic sensitivity of the C1C2EEE protein. CaM and 15 N-labeled CaM were expressed in E. coli Rosetta 2 cells and purified as described previously (42). Stock solutions of C1C2 and C1C2EEE were stored in a buffer containing 25 mM Tris, 350 mM NaCl, and 2 mM TCEP, pH 7.0; stock solutions of the motif were stored in buffer containing 20 mM Tris, 50 mM NaCl, 2 mM TCEP, pH 6.8; and stock solutions of CaM were stored in a buffer containing 50 mM MOPS, 150 mM NaCl, and 10 mM CaCl 2 , pH 7.4.…”
Section: Methodsmentioning
confidence: 99%